Menopause is a natural stage of aging: a qualitative study - I. M. P. S. Ilankoon; K. Samarasinghe; C. Elgán (BMC, 2021)
Abstract Background Menopause is a biopsychosocial phenomenon encompassing the transition in a woman's life from being fertile to infertile. Although menopause may result in extremely unpleasant physical symptoms there is evidence of a low rate of reported menopausal symptoms amongst women in Asian cultures. Women's experiences, views, and responses to menopause which influences women's daily life and well-being, may vary between different societies and cultures. This study aimed to explore and describe menopausal experiences among women in Sri Lanka. Methods A qualitative exploratory research was conducted among postmenopausal women of 46-55 years of age in the western province of Sri Lanka. Individual interviews with a purposive sample of 20 women were conducted, and data analysis was done using manifest and latent content analysis. Results The results consist of an overall theme, "Menopause is a natural stage of aging" and three categories "Entering a new stage", "Managing menopause" and "Not the end of life" which emerged from 34 codes. The overall theme highlights that changes in menopause were experienced as a natural change in life, with health problems that are normal for this change and handled with different self-care practices. The category "Entering a new stage" describes the women becoming aware of menopause and its bodily changes. The category "Managing menopause" describes women's experiences of being able to find their own remedies to ease the menopausal symptoms and by engaging in religious activities and focusing on interaction with people. The category, "Not the end of life" describes women's views of themselves as still valuable because menopause was experienced as a natural part of their lives. Conclusion Women in Sri Lanka managed menopausal problem mainly on their own as they viewed the menopause as a natural stage of aging risking unnecessary suffering and failure to detect preventable complications. Enabling support groups for menopausal women and improving on their health-seeking behaviour by encouraging them to take part in screening for cervical and breast cancer would improve their condition. Further information on additional hormone therapy with a, subsequent follow-up and evaluation by community health nurses and/or midwives, would facilitate Sri Lankan women's transition to menopause.